Utilization of autoclaved solvent extracted sesame seed cake as a cheaper source of methionine supplementation to other plant protein sources in the feed of Clarias gariepinus. (2000)
The study was designed to find the replacement value of fishmeal (Fm) by solvent extracted sesame seed cake (SSC) in relation to the amino acid supplementation. The fishmeal was replaced by SSC in five diets at 0%, 25%,50%, 75% and 100% inclusion levels. The diets were fed to Clarias gariepinus fingerlings for a period of 42 days. The trial concluded that solvent-extracted sesame seed cake (SESSC) is better fed to C. gariepinus fingerlings supplemented at 25% level. Economically SESSC diet had the lowest incidence of cost. THe fish feed production cost is reduced by at least 25% when SESSC replaces Fm in the diet of C. gariepinus.